Caspase-1 activity affects AIM2 speck formation/stability through a negative feedback loop - Juruj, Carole; Lelogeais, Virginie; Pierini, Roberto; Perret, Magali; Py, Bénédicte F.; Jamilloux, Yvan; Broz, Petr; Ader, Florence; Faure, Mathias; Henry, Thomas (Frontiers in Cellular and Infection Microbiology, 2013)
The inflammasome is an innate immune signaling platform leading to caspase-1 activation, maturation of pro-inflammatory cytokines and cell death. Recognition of DNA within the host cytosol induces the formation of a large complex composed of the AIM2 receptor, the ASC adaptor and the caspase-1 effector. Francisella tularensis, the agent of tularemia, replicates within the host cytosol. The macrophage cytosolic surveillance system detects Francisella through the AIM2 inflammasome. Upon Francisella novicida infection, we observed a faster kinetics of AIM2 speck formation in ASCKO and Casp1KO as compared to WT macrophages. This observation was validated by a biochemical approach thus demonstrating for the first time the existence of a negative feedback loop controlled by ASC/caspase-1 that regulates AIM2 complex formation/stability. This regulatory mechanism acted before pyroptosis and required caspase-1 catalytic activity. Our data suggest that sublytic caspase-1 activity could delay the formation of stable AIM2 speck, an inflammasome complex associated with cell death.